2019
DOI: 10.1111/apm.12980
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling suppresses CD14+ monocytes cells activity in patients with chronic hepatitis C

Abstract: Z. Notch signaling suppresses CD14 + monocytes cells activity in patients with chronic hepatitis C, APMIS 2019; 127: 642-652.Hepatitis C virus (HCV) infection always leads to chronic hepatitis via dysregulation of host immunity. Notch signaling also modulates the response of monocytes/macrophages. Thus, we aimed to investigate the regulatory role of Notch signaling to CD14 + monocytes. Forty patients with chronic hepatitis C and twenty normal controls (NC) were enrolled. CD14 + monocytes and CD4 + T cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…CD14 + monocytes are important components of innate immune response, and take part in the immunopathogenesis of autoimmune disorders, cancers, and infectious diseases. As the indirect antigen presenting cells and co-stimulatory signaling transducer, CD14 + monocytes induced the activation and differentiation of CD4 + T cells in rheumatoid arthritis [31], lung squamous carcinoma [32], and chronic hepatitis C [33]. In consistent with these previous reports, we found that CD14 + monocytes from patients with Kawasaki disease only effectively promoted the activation and differentiation of naïve CD4 + T cells into IFN-γ-producing Th1 and IL-17A-producing Th17 cells under direct contact condition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CD14 + monocytes are important components of innate immune response, and take part in the immunopathogenesis of autoimmune disorders, cancers, and infectious diseases. As the indirect antigen presenting cells and co-stimulatory signaling transducer, CD14 + monocytes induced the activation and differentiation of CD4 + T cells in rheumatoid arthritis [31], lung squamous carcinoma [32], and chronic hepatitis C [33]. In consistent with these previous reports, we found that CD14 + monocytes from patients with Kawasaki disease only effectively promoted the activation and differentiation of naïve CD4 + T cells into IFN-γ-producing Th1 and IL-17A-producing Th17 cells under direct contact condition.…”
Section: Discussionmentioning
confidence: 99%
“…In consistent with these previous reports, we found that CD14 + monocytes from patients with Kawasaki disease only effectively promoted the activation and differentiation of naïve CD4 + T cells into IFN-γ-producing Th1 and IL-17A-producing Th17 cells under direct contact condition. Furthermore, various factors, including CD147 [31], IL-7 [32], and Notching signaling pathway [33], could directly regulate the differential activity of CD14 + monocytes. IL-35 also dampened CD14 + monocytes-induced naïve CD4 + T cells activation in Kawasaki disease, indicating that elevated IL-35 might play a protective role to suppress extensive adaptive immune response in Kawasaki disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low-level control was defined as the LDH level in HUVECs cultured alone, while the high-level control was defined as the LDH level in Triton X-100 treated HUVECs. The frequency of target cell death was calculated using the following equation: (experiment value -low-level control)/(high-level control -low-level control) × 100% [21].…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…CD14 + monocytes are important components of innate immune response, and take part in the immunopathogenesis of autoimmune disorders, cancers, and infectious diseases. As the indirect antigen presenting cells and co-stimulatory signaling transducer, CD14 + monocytes induced the activation and differentiation of CD4 + T cells in rheumatoid arthritis [32], lung squamous carcinoma[33], and chronic hepatitis C[21]. In consistent with these previous reports, we found that CD14 + monocytes from patients with Kawasaki disease only effectively promoted the activation and differentiation of naïve CD4 + T cells into IFN-γ-producing Th1 and IL-17A-producingTh17 cells under direct contact condition.…”
mentioning
confidence: 99%